Mood Disorders and Anxiety Between Gastritis in Nursing Students - Deffi Okta Hadi Prassetia; Andikawati Fitriasari; Yurike Septianingrum; Nur Ainiyah; Syiddatul Budury (Universitas Respati Yogyakarta, 2023)
Students are very vulnerable to experiencing psychological disorders, especially mood disorders, anxiety, and depression. Disturbed psychological and emotional conditions result in the digestive system, namely gastritis. This study aims to determine the relationship between Mood Disorder and anxiety with the occurrence of gastritis symptoms in nursing students at the Faculty of Nursing and Midwifery, Nahdlatul Ulama University, Surabaya. The research method used is quantitative with a cross-sectional study. The sampling technique used was stratified random sampling with two strata (Class of 2018 and 2019). The number of samples is 125 participants. They measured instrument mood disorders using Mood Disorder Questionnaire (MDQ) and Hamilton Anxiety Range Scale (HARS). Analysis of the data used is Spearman's rank test. The statistical test results of this study found a relationship between Mood Disorder with symptoms of gastritis in nursing students with a p-value of 0.000 ≤ 0.05, and there is a relationship between anxiety with symptoms of gastritis in nursing students with a p-value of 0.001 ≤ 0.05. There is a significant relationship between mood disorders and anxiety with gastritis symptoms in nursing students. Psychological management of students is crucial in preventing symptoms of gastritis in students